2018
DOI: 10.5005/jp-journals-10054-0051
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Saliva for Measurement of Thyroid Hormones

Abstract: with more stability at room temperature, less chances of transmission of blood-borne diseases, minimum precautions for storage with minimal or no need of preservatives, and no need of special training for the laboratory personnel to handle saliva sample. [1][2][3] Its use in monitoring endocrine disorders including Cushing's syndrome, adrenal insufficiency, ovarian function disturbances, testicular diseases, hyperthyroidism, etc. 1,3,4 has been studied.Studies on hormone measurement in saliva have shown that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 114 publications
0
1
0
Order By: Relevance
“…Samples in this study were collected during the daytime, between 9 am and 4 pm. Previous studies have reported that estriol and thyroid-stimulating hormone (TSH) in saliva remain relatively stable during daylight hours [ 36 , 37 ]. Conversely, cortisol concentrations typically rise after awakening, reaching peak levels around 30 min after awakening, and then continuously decline throughout the day [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Samples in this study were collected during the daytime, between 9 am and 4 pm. Previous studies have reported that estriol and thyroid-stimulating hormone (TSH) in saliva remain relatively stable during daylight hours [ 36 , 37 ]. Conversely, cortisol concentrations typically rise after awakening, reaching peak levels around 30 min after awakening, and then continuously decline throughout the day [ 38 ].…”
Section: Discussionmentioning
confidence: 99%